Microbiota medicine: towards clinical revolution - Gebrayel, Prisca; Nicco, Carole; Al Khodor, Souhaila; Bilinski, Jaroslaw; Caselli, Elisabetta; Comelli, Elena M.; Egert, Markus; Giaroni, Cristina; Karpinski, Tomasz M.; Loniewski, Igor; Mulak, Agata; Reygner, Julie; et al. (Journal of translational medicine, 2022)
The human gastrointestinal tract is inhabited by the largest microbial community within the human body consisting of trillions of microbes called gut microbiota. The normal flora is the site of many physiological functions such as enhancing the host immunity, participating in the nutrient absorption and protecting the body against pathogenic microorganisms. Numerous investigations showed a bidirectional interplay between gut microbiota and many organs within the human body such as the intestines, the lungs, the brain, and the skin. Large body of evidence demonstrated, more than a decade ago, that the gut microbial alteration is a key factor in the pathogenesis of many local and systemic disorders. In this regard, a deep understanding of the mechanisms involved in the gut microbial symbiosis/dysbiosis is crucial for the clinical and health field. We review the most recent studies on the involvement of gut microbiota in the pathogenesis of many diseases. We also elaborate the different strategies used to manipulate the gut microbiota in the prevention and treatment of disorders. The future of medicine is strongly related to the quality of our microbiota. Targeting microbiota dysbiosis will be a huge challenge.